Determinants of Competitive Advantage and Institution Image - Sembiring, Noor (International Review of Management and Marketing, 2018)
The purpose of this research is: To develop the result of the study on the performance of value creation and the management of students' relation implemented by PS-MM in DKI Jakarta. Assessing competitive advantage, image of PS-MM, and confidence of student of MM study program in DKI Jakarta. To develop a model of the influence of value creation and student relationship management on the competitiveness of PS-MM in DKI Jakarta. Develop a model of value creation influence and management of student relation to student's belief and image of PS-MM in DKI Jakarta. Develop a model of competitive advantage to student's belief and image of PS-MM in DKI Jakarta. To examine the relationship modelS on PS-MM image and the belief of MM students in DKI Jakarta. The research method used is descriptive survey method and explanatory survey with unit of analysis is Higher Education which has MM Study Program in DKI Jakarta, and observation unit of PS-MM students in DKI Jakarta with sample size 262 people, according to the method of analysis used, SEM. Based on the results of the research, it is found several things as follows: Universities that have MM study programs should create values that are more closer to the desire of more than students, by opening more concentration on the needs of the students themselves. The ease of conducting the thesis should be improved. The college reputation must begin to be improved by improving the quality of its graduates. Emotional relationships of students should be further improved. In order to improve the competitiveness of PS-MM and student's belief, a value creation program that is more appropriate to the needs and wants of the students should be established. Likewise, to improve the image of Higher Education, the student management program is absolutely necessary. Keywords: Value Creation Performance, Student Relation Management, Trust, and Image. JEL Classifications: M31, M21, M10